Rancang Bangun Prototype Liquid Handling System untuk Sampel PCR Modifikasi CNC Plotter dan Finger Robotic - Shadiq, Muhammad Difa Ash; Abdi, Ferly Isnomo; Wulandari, Diah; Utama, Firman Yasa (Jurnal Rekayasa Mesin, 2023)
The development of digital technology in the medical and health fields is increasing, but manual PCR sample testing is still vulnerable to contamination by human hands and is relatively expensive. A liquid handling system, a tool for moving liquids automatically, can be a solution that is more environmentally friendly and easy to use. Modification of the CNC Plotter with a robotic finger is used as a liquid handling system tool to process liquid PCR sample extraction automatically with a high degree of accuracy. This study uses the research and development method by designing a Prototype Liquid Handling System, placing measuring cups and sample tubes, as well as designing the G-Code program and coding servo motors to test the capabilities of the Prototype Liquid Handling System system that has been designed. Based on the results of the liquid handling system prototype function test using NaCl fluid samples, it can be concluded that the higher the delay in the Arduino servo coding program, the longer the testing time. It can be concluded that the liquid handling system prototype that has been designed can be an effective solution for the PCR process using a modified CNC plotter and robotic finger by reducing the level of contamination with humans.